Up-conversion nano material as well as preparation method and application thereof

By using the structural design of NaErF4:Nd,Yb, Ce core, NaYF4:Yb intermediate shell and NaYF4 passivation shell in upconversion nanomaterials, combined with fine ion doping and energy transfer mechanisms, the blue-ultraviolet in the existing technology is solved. The problem of low light emission efficiency has achieved efficient blue-ultraviolet light emission performance and is suitable for photodynamic therapy and other fields.

CN119463878APending Publication Date: 2025-02-18GUANGZHOU UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411551277.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing upconverting nanomaterials have shortcomings in achieving blue-ultraviolet emission, especially due to the concentration quenching phenomenon caused by excessive Tm3+ concentration, which reduces the luminous efficiency.

Method used

NaErF4:Nd,Yb,Ce as the core and NaYF4:Yb as the intermediate shell, and the NaYF4 passivation shell is coated on the outside. Through fine ion doping and energy transfer mechanisms, the efficient upconversion blue-ultraviolet light emission of Er3+ is achieved.

Benefits of technology

It has achieved stable and excellent blue ultraviolet light emission performance under high doped rare earth ion concentration, and is suitable for photodynamic therapy and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463878A_ABST
    Figure CN119463878A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of luminescent materials, and discloses an up-conversion nano material as well as a preparation method and application thereof. The up-conversion nano material comprises a core, the element composition of the core is NaErF4: Nd, Yb and Ce, and the molar weight of Nd accounts for 2%-15% of the total molar weight of rare earth elements of the core; the core is coated with a middle shell, the element composition of the middle shell is NaYF4: Yb, and the molar weight of Yb accounts for 20%-100% of the total molar weight of rare earth elements of the middle shell; the outer part of the middle shell is coated with a passivation shell, and the element composition of the passivation shell is NaYF4. According to the up-conversion nano material, through fine ion doping and a unique energy transfer mechanism, efficient up-conversion blue and ultraviolet light emission of Er < 3 + > can be achieved; the preparation method of the up-conversion nano material is simple in process, easy to operate, low in cost, short in period and suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of luminescent materials, and in particular to an up-conversion nano material and a preparation method and application thereof. Background Art

[0002] Upconversion luminescent materials are a class of materials with unique luminescent properties. They can convert low-energy photons (such as near-infrared light) into high-energy photons (such as visible light) through the anti-Stokes effect. This process is called upconversion. Compared with other fluorescent materials, upconversion luminescent materials have the advantages of narrow emission band, long fluorescence lifetime, small autofluorescence background and good biocompatibility. In addition to their applications in optoelectronic devices, solar cells and display technology, they also show broad application prospects in the field of biology, especially in bioimaging and photodynamic therapy.

[0003] Photodynamic therapy (PDT) is a treatment method based on photosensitizers and light irradiation of specific wavelengths. It is widely used in the treatment of tumors, skin diseases and certain infectious diseases. It is well known that most photosensitizers are only sensitive to ultraviolet light and visible light, while upconversion nanomaterials can convert near-infrared light into ultraviolet-visible light. When upconversion nanoparticles with blue-ultraviolet emission light are introduced into the photosensitizer and photodynamic therapy is performed, under the excitation of near-infrared light, the photosensitizer will undergo fluorescence resonance with the blue-ultraviolet emission light generated by the upconversion nanoparticles to produce reactive oxygen species (ROS), thereby oxidizing and destroying various biomacromolecules in tissues and cells, prompting cancer cells to enter apoptosis or necrosis, thereby achieving a therapeutic effect.

[0004] However, the existing research on upconversion nanomaterials is mainly focused on their red and green light emission, while there is little research on their blue-ultraviolet light emission. This is mainly because the realization of blue-ultraviolet light emission requires specific doping ions and complex energy transfer processes. 3+ It is a common method to achieve blue-ultraviolet light emission from upconversion nanomaterials, but when Tm 3+ When the concentration is too high, concentration quenching is likely to occur, that is, the interaction between ions is enhanced, resulting in reduced luminescence efficiency or even luminescence quenching. Therefore, the development of an upconversion nanomaterial that can achieve efficient blue-ultraviolet light emission is of great significance for its research in the field of photodynamic therapy. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an up-conversion nanomaterial and a preparation method and application thereof.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] In the first aspect, the present invention provides an upconversion nanomaterial, which includes a core, the elemental composition of the core is NaErF4:Nd,Yb,Ce, wherein the molar amount of Nd accounts for 2%-15% of the total molar amount of rare earth elements in the core; the outside of the core is coated with an intermediate shell, the elemental composition of the intermediate shell is NaYF4:Yb, wherein the molar amount of Yb accounts for 20%-100% of the total molar amount of rare earth elements in the intermediate shell; the outside of the intermediate shell is coated with a passivation shell, and the elemental composition of the passivation shell is NaYF4.

[0008] The upconversion nanomaterial of the present invention has a unique core-intermediate shell-passivation shell structure, with NaErF4:Nd,Yb,Ce as the core, and NaYF4:Yb intermediate shell and NaYF4 passivation shell coated on the core in sequence; through fine ion doping and unique energy transfer mechanism, Er 3+ The upconversion nanomaterial has a core-intermediate shell-passivation shell structure, and Nd is doped in the core. 3+ 、Ce 3+ and Yb 3+ , with Nd 3+ As an energy transfer station. 3+ The energy is stored in Nd 3+ middle(( 4 F 9 / 2 (Er 3+ )→ 4 F 9 / 2 (Nd 3+ )), and then transfers the energy back to Er by cross relaxation 3+ ( 4 I 11 / 2 (Er 3+ )+ 4 F 9 / 2 (Nd 3+ )→ 4 G 11 / 2 (Er 3+ )+ 4 I 9 / 2 (Nd 3+ )), thus obtaining the rare Er 3+ Up-convert blue-ultraviolet light emission; furthermore, using Ce 3 + The guidance of energy is maximized in 4 I 11 / 2 energy level, and construct Yb-doped 3+ The intermediate shell of Yb 3+ Energy migration between Yb 3+ For Er 3+ The energy back transfer effect synergistically improves Er3+ Up-converted blue-ultraviolet emission intensity; in addition, pure Y 3+ The environmental passivation shell further protects the core and intermediate shell inside the upconversion nanomaterial, reduces the interference of the external environment on its luminescence performance, and ensures the integrity and stability of the internal structure. The unique core-intermediate shell-passivation shell structure design of the upconversion nanomaterial of the present invention and the synergistic effect of multiple doped ions enable the upconversion nanomaterial of the present invention to have stable and excellent blue-ultraviolet light emission performance at high doped rare earth ion concentrations.

[0009] As a preferred embodiment of the upconversion nanomaterial of the present invention, the molar amount of Nd in the elemental composition of the core accounts for 2%-8% of the total molar amount of rare earth elements in the core; the molar amount of Yb in the elemental composition of the intermediate shell accounts for 50%-100% of the total molar amount of rare earth elements in the intermediate shell.

[0010] Preferably, the molar amount of Nd in the elemental composition of the core accounts for 5% of the total molar amount of rare earth elements in the core; and the molar amount of Yb in the elemental composition of the intermediate shell accounts for 80% of the total molar amount of rare earth elements in the intermediate shell.

[0011] As a preferred embodiment of the upconversion nanomaterial of the present invention, the molar amount of Yb in the elemental composition of the core accounts for 5%-15% of the total molar amount of rare earth elements in the core; the molar amount of Ce in the elemental composition of the core accounts for 5%-10% of the total molar amount of rare earth elements in the core.

[0012] Preferably, the molar amount of Yb in the elemental composition of the core accounts for 10% of the total molar amount of rare earth elements in the core; the molar amount of Ce in the elemental composition of the core accounts for 8% of the total molar amount of rare earth elements in the core.

[0013] As a preferred embodiment of the upconversion nanomaterial of the present invention, the molar ratio of the core, the intermediate shell and the passivation shell is 1:(0.8-1.2):(0.9-1.5).

[0014] Preferably, the molar ratio of the core, the intermediate shell and the passivation shell is 1:1:1.

[0015] As a preferred embodiment of the upconversion nanomaterial of the present invention, the average particle size of the core is 9.76nm-11.33nm; the thickness of the intermediate shell is 2.55nm-2.93nm; and the thickness of the passivation shell is 4.06nm-5.01nm.

[0016] Preferably, the average particle size of the core is 11.03 nm; the thickness of the intermediate shell is 2.8 nm; and the thickness of the passivation shell is 4.36 nm.

[0017] In a second aspect, the present invention provides the use of the upconversion nanomaterial in a photosensitizer. The photosensitizer emits blue ultraviolet light under the excitation of light with a wavelength of 980nm, and can be used for photodynamic therapy to treat tumors, skin diseases, infectious diseases, etc.

[0018] The upconversion nanomaterial of the present invention has efficient and stable blue-ultraviolet light emission performance. This unique optical property makes it have broad application prospects in the biomedical field, especially in treatment or imaging techniques that require light excitation of a specific wavelength. For example, it can be used to prepare photosensitizers for use in photodynamic therapy, which has the advantages of increasing tissue penetration depth, reducing light damage, enhancing therapeutic effects and multifunctionality.

[0019] In a third aspect, the present invention provides a method for preparing the upconversion nanomaterial, comprising the following steps:

[0020] (1) mixing oleic acid, octadecene, a bait source, a neodymium source, an ytterbium source and a cerium source uniformly, and heating the mixture to react to obtain a rare earth-oleic acid chelate;

[0021] (2) cooling the rare earth-oleic acid chelate, adding a sodium source and a fluorine source, and heating the mixture under an inert atmosphere to react, thereby obtaining NaErF4:Nd,Yb,Ce nanoparticles;

[0022] (3) mixing oleic acid, octadecene, yttrium-oleic acid chelate and ytterbium-oleic acid chelate uniformly, adding the NaErF4:Nd,Yb,Ce nanoparticles, a sodium source and a fluorine source, and heating the mixture under an inert atmosphere to react to obtain NaErF4:Nd,Yb,Ce@NaYF4:Yb nanoparticles;

[0023] (4) Evenly mixing the yttrium-oleic acid chelate and the NaErF4:Nd,Yb,Ce@NaYF4:Yb nanoparticles, adding a sodium source and a fluorine source, and heating the mixture under an inert atmosphere to react, thereby obtaining the upconversion nanomaterial.

[0024] In the preparation method of the upconversion nanomaterial of the present invention, oleic acid, octadecene, a rare earth element source, a rare earth element-oleic acid chelate, a sodium source and a fluorine source are subjected to a coprecipitation reaction to obtain the upconversion nanomaterial; the preparation process is simple and easy to operate, has low cost, short cycle, and is suitable for mass production.

[0025] As a preferred embodiment of the up-conversion nanomaterial preparation method of the present invention, the bait source is at least one of bait chloride, erbium nitrate, and bait acetate; the neodymium source is at least one of neodymium chloride, neodymium nitrate, and neodymium acetate; the ytterbium source is at least one of ytterbium chloride, ytterbium nitrate, and ytterbium acetate; the cerium source is at least one of cerium chloride, cerium nitrate, and cerium acetate; the sodium source is at least one of sodium hydroxide and sodium fluoride; and the fluorine source is at least one of ammonium fluoride and ammonium bifluoride.

[0026] Preferably, the bait source is bait chloride; the neodymium source is neodymium chloride; the ytterbium source is ytterbium chloride; the cerium source is cerium chloride; the sodium source is sodium hydroxide; and the fluorine source is ammonium fluoride.

[0027] As a preferred embodiment of the method for preparing upconversion nanomaterials of the present invention, in step (2), step (3) and / or step (4), the temperature of the heating reaction under an inert atmosphere is 270°C-290°C, and the time is 0.5h-5h.

[0028] Preferably, in step (2), step (3) and / or step (4), the heating reaction temperature under an inert atmosphere is 280° C. and the time is 1 hour.

[0029] Compared with the prior art, the invention has the following beneficial effects: firstly, the upconversion nanomaterial of the invention uses NaErF4:Nd,Yb,Ce as the core, and sequentially coats the core with NaYF4:Yb intermediate shell and NaYF4 passivation shell; through fine ion doping and energy transfer mechanism, Er 3+ Highly efficient up-conversion of blue-ultraviolet light emission; secondly, the up-conversion nanomaterial of the present invention can be used to prepare photosensitizers for use in photodynamic therapy, which has the advantages of increasing tissue penetration depth, reducing light damage, enhancing therapeutic effects and multifunctionality; in addition, the preparation method of the up-conversion nanomaterial of the present invention is simple and easy to operate, low in cost, short in cycle, and suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A schematic diagram of energy transition of the up-conversion nanomaterial of the present invention;

[0031] Figure 2 Transmission electron microscopy images of the upconversion nanomaterial of Example 1 of the present invention: (a) core, (b) core-intermediate shell, (c) core-intermediate shell-passivation shell;

[0032] Figure 3 The fluorescence spectra of the upconversion nanomaterials of Examples 1-5 of the present invention;

[0033] Figure 4 The fluorescence spectra of the upconversion nanomaterials of Examples 5 and 6 of the present invention;

[0034] Figure 5 The fluorescence spectra of the upconversion nanomaterials of Examples 6 and 7 of the present invention;

[0035] Figure 6 The fluorescence spectra of the upconversion nanomaterials of Examples 7-11 of the present invention and the comparative example are shown. DETAILED DESCRIPTION

[0036] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0037] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, equipment, etc. used, unless otherwise specified, can be obtained from commercial sources.

[0038] The present invention provides a method for preparing the upconversion nanomaterial, comprising the following steps:

[0039] (1) mixing oleic acid, octadecene, a bait source, a neodymium source, an ytterbium source and a cerium source uniformly, and heating the mixture to react to obtain a rare earth-oleic acid chelate;

[0040] (2) cooling the rare earth-oleic acid chelate, adding a sodium source and a fluorine source, and heating the mixture under an inert atmosphere to react to obtain NaErF4:Nd,Yb,Ce nanoparticles;

[0041] (3) mixing oleic acid, octadecene, yttrium-oleic acid chelate and ytterbium-oleic acid chelate uniformly, adding the NaErF4:Nd,Yb,Ce nanoparticles, a sodium source and a fluorine source, and heating the mixture under an inert atmosphere to react to obtain NaErF4:Nd,Yb,Ce@NaYF4:Yb nanoparticles;

[0042] (4) Evenly mixing the yttrium-oleic acid chelate and the NaErF4:Nd,Yb,Ce@NaYF4:Yb nanoparticles, adding a sodium source and a fluorine source, and heating the mixture under an inert atmosphere to react, thereby obtaining the upconversion nanomaterial.

[0043] In one embodiment, in step (1), the volume ratio of oleic acid to octadecene is (0.65-0.85):1.

[0044] In one embodiment, in step (1), the volume ratio of oleic acid to octadecene is 0.75:1.

[0045] In one embodiment, in step (1), the erbium source is an erbium salt solution; the concentration of the erbium salt solution is 0.4-0.6 mol / L; the neodymium source is a neodymium salt solution; the concentration of the neodymium salt solution is 0.08-0.12 mol / L; the ytterbium source is an ytterbium salt solution; the concentration of the ytterbium salt solution is 0.4-0.6 mol / L, and the cerium source is a cerium salt solution; the concentration of the cerium salt solution is 0.08-0.12 mol / L.

[0046] In one embodiment, in step (1), the erbium source is an erbium salt solution; the concentration of the erbium salt solution is 0.5 mol / L; the neodymium source is a neodymium salt solution; the concentration of the neodymium salt solution is 0.01 mol / L; the ytterbium source is an ytterbium salt solution; the concentration of the ytterbium salt solution is 0.45 mol / L; the cerium source is a cerium salt solution; the concentration of the cerium salt solution is 0.1 mol / L.

[0047] In one embodiment, in step (1), the erbium source is an erbium salt solution; the neodymium source is a neodymium salt solution; the ytterbium source is an ytterbium salt solution; the cerium source is a cerium salt solution; and the solvent of the erbium salt solution, the neodymium salt solution, the ytterbium salt solution and the cerium salt solution is water.

[0048] In one embodiment, in step (1), the erbium source is an erbium salt solution; and the volume ratio of the oleic acid to the erbium salt solution is 15:(1.5-1.7).

[0049] In one embodiment, in step (1), the erbium source is an erbium salt solution; and the volume ratio of the oleic acid to the erbium salt solution is 15:1.54.

[0050] In one embodiment, in step (1), the neodymium source is a neodymium salt solution; and the volume ratio of oleic acid to the neodymium salt solution is 15:(0-1.5).

[0051] In one embodiment, in step (1), the neodymium source is a neodymium salt solution; and the volume ratio of the oleic acid to the neodymium salt solution is 15:0.5.

[0052] In one embodiment, in step (1), the ytterbium source is an ytterbium salt solution; and the volume ratio of the oleic acid to the ytterbium salt solution is 15:(0.2-0.8).

[0053] In one embodiment, in step (1), the ytterbium source is an ytterbium salt solution; and the volume ratio of the oleic acid to the ytterbium salt solution is 15:0.2.

[0054] In one embodiment, in step (1), the cerium source is a cerium salt solution; and the volume ratio of the oleic acid to the cerium salt solution is 15:(0.02-1).

[0055] In one embodiment, in step (1), the cerium source is a cerium salt solution; and the volume ratio of the oleic acid to the cerium salt solution is 15:0.8.

[0056] In one embodiment, in step (1), the heating reaction temperature is 145-155° C. and the time is 1-1.5 h.

[0057] In one embodiment, in step (1), the heating reaction temperature is 150° C. and the time is 1.2 h.

[0058] In one embodiment, in step (2), the sodium source is a methanol solution of sodium hydroxide; the concentration of the sodium hydroxide is 0.2 mol / L-0.8 mol / L.

[0059] In one embodiment, in step (2), the sodium source is a methanol solution of sodium hydroxide; the concentration of the sodium hydroxide is 0.5 mol / L.

[0060] In one embodiment, in step (2), the fluorine source is a methanol solution of ammonium fluoride; the concentration of the ammonium fluoride is 0.5 mol / L-1 mol / L.

[0061] In one embodiment, in step (2), the fluorine source is a methanol solution of ammonium fluoride; and the concentration of the ammonium fluoride is 0.8 mol / L.

[0062] In one embodiment, in step (2), the sodium source is a methanol solution of sodium hydroxide; the fluorine source is a methanol solution of ammonium fluoride; and the volume ratio of the methanol solution of sodium hydroxide to the methanol solution of ammonium fluoride is (0.8-1.2):1.

[0063] In one embodiment, in step (2), the sodium source is a methanol solution of sodium hydroxide; the fluorine source is a methanol solution of ammonium fluoride; and the volume ratio of the methanol solution of sodium hydroxide to the methanol solution of ammonium fluoride is 1:1.

[0064] In one embodiment, in step (2), the sodium source is a methanol solution of sodium hydroxide; the volume ratio of the oleic acid to the methanol solution of sodium hydroxide is (4-8):1.

[0065] In one embodiment, in step (2), the sodium source is a methanol solution of sodium hydroxide; and the volume ratio of the oleic acid to the methanol solution of sodium hydroxide is 5:1.

[0066] In one embodiment, in step (2), the inert atmosphere comprises nitrogen.

[0067] In one embodiment, in step (3), the volume ratio of oleic acid to octadecene is (1.8-2.2):3.

[0068] In one embodiment, in step (3), the volume ratio of oleic acid to octadecene is 2:3.

[0069] In one embodiment, in step (3), the method for preparing the yttrium-oleic acid chelate comprises the following steps: uniformly mixing oleic acid, octadecene and a yttrium source, and heating the mixture for reaction.

[0070] In one embodiment, in step (3), the method for preparing the ytterbium-oleic acid chelate comprises the following steps: uniformly mixing oleic acid, octadecene and ytterbium source, and heating for reaction.

[0071] In one embodiment, in step (3), the yttrium source in the preparation method of the yttrium-oleic acid chelate is a yttrium salt solution, and the concentration of the yttrium salt solution is 0.035mol / L-0.045mol / L; the ytterbium source in the preparation method of the ytterbium-oleic acid chelate is a ytterbium salt solution, and the concentration of the ytterbium salt solution is 0.035mol / L-0.045mol / L.

[0072] In one embodiment, in step (3), the yttrium source in the preparation method of the yttrium-oleic acid chelate is a yttrium salt solution, and the concentration of the yttrium salt solution is 0.04 mol / L; the ytterbium source in the preparation method of the ytterbium-oleic acid chelate is a ytterbium salt solution, and the concentration of the ytterbium salt solution is 0.04 mol / L.

[0073] In one embodiment, in step (3), the volume ratio of oleic acid to yttrium-oleic acid chelate is 10:(0-2); the volume ratio of oleic acid to ytterbium-oleic acid chelate is 10:(0.5-2.5).

[0074] In one embodiment, in step (3), the volume ratio of oleic acid to yttrium-oleic acid chelate is 10:0.5; the volume ratio of oleic acid to ytterbium-oleic acid chelate is 5:1.

[0075] In one embodiment, in step (3), the molar ratio of the NaErF4:Nd,Yb,Ce nanoparticles and yttrium-oleic acid chelate is 1:(0-1).

[0076] In one embodiment, in step (3), the molar ratio of the NaErF4:Nd,Yb,Ce nanoparticles to the yttrium-oleic acid chelate is 1:0.2.

[0077] In one embodiment, in step (3), the molar ratio of the NaErF4:Nd,Yb,Ce nanoparticles and ytterbium-oleic acid chelate is 1:(0-1).

[0078] In one embodiment, in step (3), the molar ratio of the NaErF4:Nd,Yb,Ce nanoparticles to the ytterbium-oleic acid chelate is 1:0.8.

[0079] In one embodiment, in step (3), the sodium source is a methanol solution of sodium hydroxide; the concentration of the sodium hydroxide is 0.2 mol / L-0.8 mol / L.

[0080] In one embodiment, in step (3), the sodium source is a methanol solution of sodium hydroxide; the concentration of the sodium hydroxide is 0.5 mol / L.

[0081] In one embodiment, in step (3), the fluorine source is a methanol solution of ammonium fluoride; and the concentration of the ammonium fluoride is 0.5 mol / L-1 mol / L.

[0082] In one embodiment, in step (3), the fluorine source is a methanol solution of ammonium fluoride; and the concentration of the ammonium fluoride is 0.8 mol / L.

[0083] In one embodiment, in step (3), the sodium source is a methanol solution of sodium hydroxide; the fluorine source is a methanol solution of ammonium fluoride; and the volume ratio of the methanol solution of sodium hydroxide to the methanol solution of ammonium fluoride is (0.8-1.2):1.

[0084] In one embodiment, in step (3), the sodium source is a methanol solution of sodium hydroxide; the fluorine source is a methanol solution of ammonium fluoride; and the volume ratio of the methanol solution of sodium hydroxide to the methanol solution of ammonium fluoride is 1:1.

[0085] In one embodiment, in step (3), the sodium source is a methanol solution of sodium hydroxide; the volume ratio of the yttrium-oleic acid chelate to the methanol solution of sodium hydroxide is (0-2):0.5.

[0086] In one embodiment, in step (3), the sodium source is a methanol solution of sodium hydroxide; and the volume ratio of the yttrium-oleic acid chelate to the methanol solution of sodium hydroxide is 1:1.

[0087] In one embodiment, in step (3), the inert atmosphere comprises nitrogen.

[0088] In one embodiment, in step (4), the method for preparing the yttrium-oleic acid chelate comprises the following steps: uniformly mixing oleic acid, octadecene and a yttrium source, and heating the mixture for reaction.

[0089] In one embodiment, in step (4), the yttrium source in the preparation method of the yttrium-oleic acid chelate is a yttrium salt solution; the concentration of the yttrium salt solution is 0.035 mol / L-0.045 mol / L.

[0090] In one embodiment, in step (4), the yttrium source in the preparation method of the yttrium-oleic acid chelate is a yttrium salt solution; the concentration of the yttrium salt solution is 0.04 mol / L.

[0091] In one embodiment, in step (4), the molar ratio of the NaErF4:Nd,Yb,Ce@NaYF4:Yb nanoparticles and yttrium-oleic acid chelate is 1:(0.8-1.2).

[0092] In one embodiment, in step (4), the molar ratio of the NaErF4:Nd,Yb,Ce@NaYF4:Yb nanoparticles and yttrium-oleic acid chelate is 1:1.

[0093] In one embodiment, in step (4), the sodium source is a methanol solution of sodium hydroxide; the concentration of the sodium hydroxide is 0.2 mol / L-0.8 mol / L.

[0094] In one embodiment, in step (4), the sodium source is a methanol solution of sodium hydroxide; the concentration of the sodium hydroxide is 0.5 mol / L.

[0095] In one embodiment, in step (4), the fluorine source is a methanol solution of ammonium fluoride; the concentration of the ammonium fluoride is 0.5 mol / L-1 mol / L.

[0096] In one embodiment, in step (4), the fluorine source is a methanol solution of ammonium fluoride; and the concentration of the ammonium fluoride is 0.8 mol / L.

[0097] In one embodiment, in step (4), the sodium source is a methanol solution of sodium hydroxide; the fluorine source is a methanol solution of ammonium fluoride; and the volume ratio of the methanol solution of sodium hydroxide to the methanol solution of ammonium fluoride is (0.8-1.2):1.

[0098] In one embodiment, in step (4), the sodium source is a methanol solution of sodium hydroxide; the fluorine source is a methanol solution of ammonium fluoride; and the volume ratio of the methanol solution of sodium hydroxide to the methanol solution of ammonium fluoride is 1:1.

[0099] In one embodiment, in step (4), the sodium source is a methanol solution of sodium hydroxide; the volume ratio of the yttrium-oleic acid chelate to the methanol solution of sodium hydroxide is (4-6):1.

[0100] In one embodiment, in step (4), the sodium source is a methanol solution of sodium hydroxide; and the volume ratio of the yttrium-oleic acid chelate to the methanol solution of sodium hydroxide is 1:1.

[0101] In one embodiment, in step (4), the inert atmosphere comprises nitrogen.

[0102] The following is an elaboration in conjunction with specific embodiments to illustrate the practical effects of the solutions of the present invention.

[0103] In the following examples and comparative examples, the preparation methods of the yttrium-oleic acid chelate and ytterbium-oleic acid chelate involved are:

[0104] (1) Preparation of yttrium-oleic acid chelate

[0105] Dissolve YCl3 in deionized water to prepare 50mL of 0.04mol / L YCl3 solution. Place the above YCl3 solution, 20mL of oleic acid and 30mL of octadecene in a three-necked flask and stir thoroughly to mix evenly. Pass nitrogen as a protective gas and react at 105°C for 1.5h to remove moisture from the solution. Then heat to 150°C and react for 1.5h. The resulting solution is yttrium-oleic acid chelate (YCl3 concentration is 0.04mol / L).

[0106] (2) Preparation of ytterbium-oleic acid chelate

[0107] Dissolve YbCl3 in deionized water to prepare 50mL of YbCl3 solution with a concentration of 0.04mol / L. Place the above YbCl3 solution, 20mL of oleic acid and 30mL of octadecene in a three-necked flask and stir thoroughly to mix evenly. Pass nitrogen as a protective gas and react at 105°C for 1.5h to remove moisture from the solution. Then heat to 150°C and react for 1.5h. The resulting solution is ytterbium-oleic acid chelate (YbCl3 concentration is 0.04mol / L).

[0108] Example 1: Preparation of upconversion nanomaterials

[0109] (1) Preparation of core: 15 mL of oleic acid and 20 mL of octadecene were placed in a three-necked flask and stirred thoroughly to mix evenly. Then, 1.54 mL of 0.5 mol / L erbium chloride solution, 0.5 mL of 0.1 mol / L neodymium chloride solution, 0.2 mL of 0.5 mol / L ytterbium chloride solution and 0.8 mL of 0.1 mol / L cerium chloride solution were added, stirred thoroughly to mix evenly, and then the temperature was raised to 105°C to remove water from the solution. Then, a high temperature reaction was carried out at 150°C for 1.5 hours to generate rare earth-oleic acid chelate. Then it was naturally cooled to room temperature, 5 mL of 0.5 mol / L sodium hydroxide methanol solution and 5 mL of 0.8 mol / L ammonium fluoride methanol solution were added and stirred evenly, the temperature was raised to 90°C for 1 hour, excess methanol was removed, and then a high-temperature reaction was carried out at 280°C for 1 hour under nitrogen protection; finally, the reaction mixture was naturally cooled to room temperature, washed with anhydrous ethanol, and centrifuged at 10000 rpm for 10 minutes, and centrifuged twice to obtain a pink precipitate, namely Na77% ErF4:5% Nd, 10% Yb, 8% Ce nanoparticles, which were stored in cyclohexane; wherein the molar amount of Nd in the core accounted for 5% of the total molar amount of rare earth elements in the core, the molar amount of Yb in the core accounted for 10% of the total molar amount of rare earth elements in the core, and the molar amount of Ce in the core accounted for 5% of the total molar amount of rare earth elements in the core.

[0110] (2) Coating the intermediate shell: 10 mL of oleic acid and 15 mL of octadecene are stirred in a three-necked flask and mixed evenly. Then, 0.5 mL of yttrium-oleic acid chelate (YCl3 concentration is 0.04 mol / L) and 2 mL of ytterbium-oleic acid chelate (YbCl3 concentration is 0.04 mol / L) are added and mixed evenly. The Na77% ErF4:5% Nd, 10% Yb, 8% Ce nanoparticles prepared in step (1) are added, and then 0.5 mL of 0.5 mol / L sodium hydroxide methanol solution and 0.5 mL of 0.8 mol / L ammonium fluoride methanol solution are added and stirred, and the temperature is raised to 90°C, maintained for 45 minutes, and excess methanol is removed. Then, under nitrogen protection, the reaction was carried out at a high temperature of 280°C for 1 hour, and finally naturally cooled to obtain Na77%ErF4:5%Nd,10%Yb,8%Ce@Na20%YF4:80%Yb core-shell structured nanoparticles, which were stored in cyclohexane; among them, the molar amount of Yb in the middle shell accounted for 80% of the total molar amount of rare earth elements in the middle shell.

[0111] (3) Passivation shell coating: 2.5 mL of yttrium-oleic acid chelate (YCl3 concentration of 0.04 mol / L) was added to the reaction solution after natural cooling in step (2) and stirred evenly. Then 0.5 mL of 0.5 mol / L sodium hydroxide methanol solution and 0.5 mL of 0.8 mol / L ammonium fluoride methanol solution were added and stirred, and the temperature was raised to 90°C, maintained for 45 min, and excess methanol was removed. Then, under nitrogen protection, the high temperature reaction was carried out at 280°C for 1 h. Finally, the reaction mixture was naturally cooled to room temperature, washed with anhydrous ethanol, and centrifuged at 10000 rpm for 10 min, centrifuged twice, and a precipitate was obtained, which was Na77% ErF4:5% Nd, 10% Yb, 8% Ce@Na20% YF4:80% Yb@NaYF4 upconversion nanomaterial, which was stored in cyclohexane.

[0112] Example 2: Preparation of upconversion nanomaterials

[0113] The only difference between the preparation method of the upconversion nanomaterial described in this embodiment and that in Example 1 is that 0.5 mL of yttrium-oleic acid chelate (YCl3 concentration is 0.04 mol / L) and 2 mL of ytterbium-oleic acid chelate (YbCl3 concentration is 0.04 mol / L) in step (2) of Example 1 are replaced by 2 mL of yttrium-oleic acid chelate (YCl3 concentration is 0.04 mol / L) and 0.5 mL of ytterbium-oleic acid chelate (YbCl3 concentration is 0.04 mol / L). The structural formula of the upconversion nanomaterial finally obtained is Na77%ErF4:5%Nd,10%Yb,8%Ce@Na80%YF4:20%Yb@NaYF4; wherein the molar amount of Yb in the intermediate shell accounts for 20% of the total molar amount of rare earth elements in the intermediate shell.

[0114] Example 3: Preparation of upconversion nanomaterials

[0115] The only difference between the preparation method of the upconversion nanomaterial described in this embodiment and that in Example 1 is that 0.5 mL of yttrium-oleic acid chelate (YCl3 concentration is 0.04 mol / L) and 2 mL of ytterbium-oleic acid chelate (YbCl3 concentration is 0.04 mol / L) in step (2) of Example 1 are replaced by 1.25 mL of yttrium-oleic acid chelate (YCl3 concentration is 0.04 mol / L) and 1.25 mL of ytterbium-oleic acid chelate (YbCl3 concentration is 0.04 mol / L). The structural formula of the upconversion nanomaterial finally obtained is Na77%ErF4:5%Nd,10%Yb,8%Ce@Na50%YF4:50%Yb@NaYF4; wherein the molar amount of Yb in the intermediate shell accounts for 50% of the total molar amount of rare earth elements in the intermediate shell.

[0116] Example 4: Preparation of upconversion nanomaterials

[0117] The only difference between the preparation method of the upconversion nanomaterial described in this embodiment and that in embodiment 1 is that 0.5 mL of yttrium-oleic acid chelate (YCl3 concentration is 0.04 mol / L) and 2 mL of ytterbium-oleic acid chelate (YbCl3 concentration is 0.04 mol / L) in step (2) of embodiment 1 are replaced by 2.5 mL of ytterbium-oleic acid chelate (YbCl3 concentration is 0.04 mol / L). The structural formula of the upconversion nanomaterial finally obtained is Na77%ErF4:5%Nd,10%Yb,8%Ce@NaYbF4@NaYF4; wherein the molar amount of Yb in the intermediate shell accounts for 100% of the total molar amount of rare earth elements in the intermediate shell.

[0118] Example 5: Preparation of upconversion nanomaterials

[0119] The only difference between the preparation method of the upconversion nanomaterial described in this embodiment and that in Embodiment 1 is that the coating of the intermediate shell in step (2) is not performed.

[0120] (1) Preparation of core: 15 mL of oleic acid and 20 mL of octadecene were placed in a three-necked flask and stirred thoroughly to mix evenly. Then, 1.54 mL of 0.5 mol / L erbium chloride solution, 0.5 mL of 0.1 mol / L neodymium chloride solution, 0.2 mL of 0.5 mol / L ytterbium chloride solution and 0.8 mL of 0.1 mol / L cerium chloride solution were added, stirred thoroughly to mix evenly, and then the temperature was raised to 105°C to remove water from the solution. Then, a high temperature reaction was carried out at 150°C for 1.5 hours to generate rare earth-oleic acid chelate. Then, it was naturally cooled to room temperature, 5 mL of a methanol solution of sodium hydroxide with a concentration of 0.5 mol / L and 5 mL of a methanol solution of ammonium fluoride with a concentration of 0.8 mol / L were added and stirred evenly, the temperature was raised to 90°C for 1 hour, excess methanol was removed, and then a high-temperature reaction was carried out at 280°C for 1 hour under nitrogen protection; finally, the reaction mixture was naturally cooled to room temperature, washed with anhydrous ethanol, and centrifuged at 10000 rpm for 10 minutes, and centrifuged twice to obtain a pink precipitate, namely Na77% ErF4:5% Nd, 10% Yb, 8% Ce nanoparticles, which were stored in cyclohexane; wherein the molar amount of Nd in the core accounted for 5% of the total molar amount of rare earth elements in the core, the molar amount of Yb in the core layer accounted for 10% of the total molar amount of rare earth elements in the core, and the molar amount of Ce in the core accounted for 5% of the total molar amount of rare earth elements in the core.

[0121] (2) Passivation shell coating: 10 mL of oleic acid and 15 mL of octadecene were placed in a three-necked flask and stirred thoroughly to mix evenly. Then 2.5 mL of yttrium-oleic acid chelate (YCl3 concentration is 0.04 mol / L) was added and mixed evenly. The Na77% ErF4:5% Nd, 10% Yb, 8% Ce nanoparticles prepared in step (1) were added, followed by 0.5 mL of 0.5 mol / L sodium hydroxide methanol solution and 0.5 mL of 0.8 mol / L ammonium fluoride methanol solution and stirred, heated to 90°C, maintained for 45 min, and excess methanol was removed. Then, under nitrogen protection, the reaction was carried out at a high temperature of 280°C for 1 hour. Finally, the reaction mixture was naturally cooled to room temperature, washed with anhydrous ethanol, and centrifuged at 10000 rpm for 10 minutes, for a total of 2 centrifugations to obtain a precipitate, namely Na77% ErF4:5% Nd, 10% Yb, 8% Ce@NaYF4 upconversion nanomaterials, which were stored in cyclohexane.

[0122] Example 6: Preparation of upconversion nanomaterials

[0123] The only difference between the preparation method of the upconversion nanomaterial described in this embodiment and that in Example 5 is that the 1.54 mL 0.5 mol / L erbium chloride solution, 0.5 mL 0.1 mol / L neodymium chloride solution, 0.2 mL 0.5 mol / L ytterbium chloride solution and 0.8 mL 0.1 mol / L cerium chloride solution in step (1) of Example 5 are replaced by 1.7 mL 0.5 mol / L erbium chloride solution, 0.5 mL 0.1 mol / L neodymium chloride solution and 0.2 mL 0.5 mol / L ytterbium chloride solution. The structural formula of the upconversion nanomaterial obtained is Na85%ErF4:5%Nd,10%Yb@NaYF4; wherein the molar amount of Nd in the core accounts for 5% of the total molar amount of rare earth elements in the core, and the molar amount of Yb in the core accounts for 10% of the total molar amount of rare earth elements in the core.

[0124] Example 7: Preparation of upconversion nanomaterials

[0125] The only difference between the preparation method of the upconversion nanomaterial described in this embodiment and that in Example 5 is that the 1.54 mL of 0.5 mol / L erbium chloride solution, 0.5 mL of 0.1 mol / L neodymium chloride solution, 0.2 mL of 0.5 mol / L ytterbium chloride solution and 0.8 mL of 0.1 mol / L cerium chloride solution in step (1) of Example 5 are replaced by 1.9 mL of 0.5 mol / L erbium chloride solution and 0.5 mL of 0.1 mol / L neodymium chloride solution. The structural formula of the upconversion nanomaterial obtained is Na95%ErF4:5%Nd@NaYF4; wherein the molar amount of Nd in the core accounts for 5% of the total molar amount of rare earth elements in the core.

[0126] Example 8: Preparation of upconversion nanomaterials

[0127] The only difference between the preparation method of the upconversion nanomaterial described in this embodiment and that in Example 7 is that the 1.9 mL of 0.5 mol / L erbium chloride solution and 0.5 mL of 0.1 mol / L neodymium chloride solution in step (1) of Example 7 are replaced with 1.96 mL of 0.5 mol / L erbium chloride solution and 0.2 mL of 0.1 mol / L neodymium chloride solution. The structural formula of the upconversion nanomaterial obtained is Na98%ErF4:2%Nd@NaYF4; wherein the molar amount of Nd in the core accounts for 2% of the total molar amount of rare earth elements in the core.

[0128] Example 9: Preparation of upconversion nanomaterials

[0129] The only difference between the preparation method of the upconversion nanomaterial described in this embodiment and that in Example 7 is that the 1.9 mL of 0.5 mol / L erbium chloride solution and 0.5 mL of 0.1 mol / L neodymium chloride solution in step (1) of Example 7 are replaced with 1.84 mL of 0.5 mol / L erbium chloride solution and 0.8 mL of 0.1 mol / L neodymium chloride solution. The structural formula of the upconversion nanomaterial obtained is Na92%ErF4:8%Nd@NaYF4; wherein the molar amount of Nd in the core accounts for 8% of the total molar amount of rare earth elements in the core.

[0130] Example 10: Preparation of upconversion nanomaterials

[0131] The only difference between the preparation method of the upconversion nanomaterial described in this embodiment and that in embodiment 7 is that the 1.9 mL of 0.5 mol / L erbium chloride solution and 0.5 mL of 0.1 mol / L neodymium chloride solution in step (1) of embodiment 6 are replaced by 1.8 mL of 0.5 mol / L erbium chloride solution and 1 mL of 0.1 mol / L neodymium chloride solution. The structural formula of the upconversion nanomaterial obtained is Na90%ErF4:10%Nd@NaYF4; wherein the molar amount of Nd in the core accounts for 10% of the total molar amount of rare earth elements in the core.

[0132] Example 11: Preparation of upconversion nanomaterials

[0133] The only difference between the preparation method of the upconversion nanomaterial described in this embodiment and that in embodiment 7 is that the 1.9 mL of 0.5 mol / L erbium chloride solution and 0.5 mL of 0.1 mol / L neodymium chloride solution in step (1) of embodiment 6 are replaced by 1.7 mL of 0.5 mol / L erbium chloride solution and 1.5 mL of 0.1 mol / L neodymium chloride solution. The structural formula of the upconversion nanomaterial obtained is Na85%ErF4:15%Nd@NaYF4; wherein the molar amount of Nd in the core accounts for 15% of the total molar amount of rare earth elements in the core.

[0134] Comparative Example: Preparation of Upconversion Nanomaterials

[0135] (1) Preparation of core layer: 15 mL of oleic acid and 20 mL of octadecene were placed in a three-necked flask and stirred thoroughly to mix evenly. Then, 2 mL of 0.5 mol / L erbium chloride solution was added and stirred thoroughly to mix evenly. Then, the temperature was raised to 105°C to remove the water in the solution. Then, a high temperature reaction was carried out at 150°C for 1.5 hours to generate erbium-oleic acid chelate. Then, it was naturally cooled to room temperature, 5 mL of a methanol solution of sodium hydroxide with a concentration of 0.5 mol / L and 5 mL of a methanol solution of ammonium fluoride with a concentration of 0.8 mol / L were added and stirred evenly, the temperature was raised to 90°C for 1 hour, excess methanol was removed, and then a high-temperature reaction was carried out at 280°C for 1 hour under nitrogen protection; finally, the reaction mixture was naturally cooled to room temperature, washed with anhydrous ethanol, and centrifuged at 10000 rpm for 10 minutes, and centrifuged twice to obtain a precipitate, namely NaErF4 nanoparticles, which were stored in cyclohexane; wherein the molar amount of Er in the core accounted for 100% of the total molar amount of rare earth elements in the core.

[0136] (2) Passivation shell coating: 10 mL of oleic acid and 15 mL of octadecene were placed in a three-necked flask and stirred thoroughly to mix evenly. Subsequently, 2.5 mL of yttrium-oleic acid chelate (YCl3 concentration is 0.04 mol / L) was added and mixed evenly. The NaErF4 nanoparticles prepared in step (1) were added, and then 0.5 mL of a methanol solution of 0.5 mol / L sodium hydroxide and 0.5 mL of a methanol solution of 0.8 mol / L ammonium fluoride were added and stirred, and the temperature was raised to 90°C, maintained for 45 min, and excess methanol was removed. Then, under nitrogen protection, the reaction was carried out at a high temperature of 280°C for 1 h, and finally the reaction mixture was naturally cooled to room temperature, washed with anhydrous ethanol, and centrifuged at 10000 rpm for 10 min, and centrifuged twice to obtain a precipitate, which is the NaErF4@NaYF4 upconversion nanomaterial, and stored in cyclohexane.

[0137] Test Example 1: Morphology Study of Upconversion Nanomaterials

[0138] Transmission electron microscopy was used to analyze the morphology of Na77% ErF4:5% Nd, 10% Yb, 8% Ce nanoparticles, Na77% ErF4:5% Nd, 10% Yb, 8% Ce@Na20% YF4:80% Yb core-intermediate shell structure nanoparticles and Na77% ErF4:5% Nd, 10% Yb, 8% Ce@Na20% YF4:80% Yb@NaYF4 core-intermediate shell-passivation shell structure upconversion nanomaterials prepared in Example 1.

[0139] like Figure 2 As shown, the nanoparticles obtained by the preparation method of the upconversion nanomaterial of the present invention have a pure hexagonal phase lattice structure and are highly dispersible and uniform. The average particle sizes of Na77%ErF4:5%Nd,10%Yb,8%Ce nanoparticles, Na77%ErF4:5%Nd,10%Yb,8%Ce@Na20%YF4:80%Yb core-intermediate shell structure nanoparticles and Na77%ErF4:5%Nd,10%Yb,8%Ce@Na20%YF4:80%Yb@NaYF4 core-intermediate shell-passivation shell structure upconversion nanomaterials are 11.03nm, 13.83nm and 18.19nm, respectively.

[0140] Test Example 2: Study on the fluorescence properties of upconversion nanomaterials

[0141] The fluorescence properties of the upconversion nanomaterials prepared in Examples 1-11 and the comparative example were tested using a fluorescence spectrum analyzer, and the upconversion nanomaterials were analyzed by fluorescence spectrum under 980 nm excitation.

[0142] First, if Figure 3As shown, it can be seen from the fluorescence spectra of the upconversion nanomaterials of Examples 1-5 under 980nm excitation that the upconversion nanomaterials of the present invention have a high efficiency of Er by constructing a core-shell-shell structure doped with specific rare earth ions. 3+ Up-conversion blue-ultraviolet emission performance (378nm and 408nm), and when Yb 3+ When the doping molar amount accounts for 80% of the total molar amount of the intermediate shell rare earth elements, Er 3+ The blue-ultraviolet light emission intensity reached the strongest, and its emission intensities at 378nm, 408nm, and 450nm were 5.31 times, 4.63 times, and 1.4 times that of the upconversion nanomaterials without intermediate shell construction, respectively.

[0143] Secondly, if Figure 4 As shown, from the fluorescence spectra of the upconversion nanomaterials of Example 5 and Example 6 under 980nm excitation, it can be seen that the appropriate molar amount of Ce in the core of the upconversion nanomaterial of the present invention 3+ , can be used with Er 3+ The cross-relaxation effect between them significantly increases the Er 3+ The emission intensity of blue ultraviolet light at 378 and 408 nm is respectively 3+ 20 times and 15.2 times. Figure 5 As shown, from the fluorescence spectra of the upconversion nanomaterials of Example 6 and Example 7 under 980nm excitation, it can be seen that the upconversion nanomaterials of the present invention introduce an appropriate molar amount of Yb into the core. 3+ , you can use Yb 3+ The energy transfer effect effectively enhances the Er at 378nm and 408nm 3+ The emission intensities of blue-ultraviolet light at 378 and 408 nm are respectively 3+ 4.6 and 5.1 times of the same period. Figure 6 As shown, from the fluorescence spectra of the up-conversion nanomaterials of Examples 7-11 and the comparative example under 980nm excitation, it can be seen that when the molar amount of Nd in the core accounts for 5% of the total molar amount of the core rare earth elements, the up-conversion nanomaterial has the highest Er 3+ Blue UV (378nm and 408nm) emission intensity.

[0144] Therefore, the unique core-intermediate shell-passivation shell structure design of the upconversion nanomaterial of the present invention and the synergistic effect of multiple doped ions enable the upconversion nanomaterial of the present invention to have stable and excellent blue-ultraviolet light emission performance at a high concentration of doped rare earth ions.

[0145] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. An upconversion nanomaterial, characterized in that: The upconversion nanomaterial comprises a core, the element composition of the core is NaErF4:Nd,Yb,Ce, wherein the molar amount of Nd accounts for 2%-15% of the total molar amount of rare earth elements in the core; the outside of the core is coated with an intermediate shell, the element composition of the intermediate shell is NaYF4:Yb, wherein the molar amount of Yb accounts for 20%-100% of the total molar amount of rare earth elements in the intermediate shell; the outside of the intermediate shell is coated with a passivation shell, the element composition of the passivation shell is NaYF4.

2. The upconversion nanomaterial according to claim 1, characterized in that: The molar amount of Nd in the element composition of the core accounts for 2%-8% of the total molar amount of rare earth elements in the core; the molar amount of Yb in the element composition of the intermediate shell accounts for 50%-100% of the total molar amount of rare earth elements in the intermediate shell.

3. The upconversion nanomaterial according to claim 2, characterized in that: The molar amount of Nd in the element composition of the core accounts for 5% of the total molar amount of rare earth elements in the core; the molar amount of Yb in the element composition of the intermediate shell accounts for 80% of the total molar amount of rare earth elements in the intermediate layer.

4. The upconversion nanomaterial according to claim 1, characterized in that: The molar amount of Yb in the element composition of the core accounts for 5%-15% of the total molar amount of rare earth elements in the core; the molar amount of Ce in the element composition of the core accounts for 5%-10% of the total molar amount of rare earth elements in the core.

5. The upconversion nanomaterial according to claim 1, characterized in that: The molar ratio of the core, the intermediate shell and the passivation shell is 1:(0.8-1.2):(0.9-1.5).

6. The upconversion nanomaterial according to claim 1, characterized in that: The average particle size of the core is 9.76nm-11.33nm; the thickness of the intermediate shell is 2.55nm-2.93nm; and the thickness of the passivation shell is 4.06nm-5.01nm.

7. Use of the upconversion nanomaterial according to any one of claims 1 to 6 in a photosensitizer.

8. The method for preparing the upconversion nanomaterial according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) mixing oleic acid, octadecene, a bait source, a neodymium source, an ytterbium source and a cerium source uniformly, and heating the mixture to react to obtain a rare earth-oleic acid chelate; (2) cooling the rare earth-oleic acid chelate, adding a sodium source and a fluorine source, and heating the mixture under an inert atmosphere to react to obtain NaErF4:Nd,Yb,Ce nanoparticles; (3) mixing oleic acid, octadecene, yttrium-oleic acid chelate and ytterbium-oleic acid chelate uniformly, adding the NaErF4:Nd,Yb,Ce nanoparticles, a sodium source and a fluorine source, and heating the mixture under an inert atmosphere to react to obtain NaErF4:Nd,Yb,Ce@NaYF4:Yb nanoparticles; (4) Evenly mixing the yttrium-oleic acid chelate and the NaErF4:Nd,Yb,Ce@NaYF4:Yb nanoparticles, adding a sodium source and a fluorine source, and heating the mixture under an inert atmosphere to react, thereby obtaining the upconversion nanomaterial.

9. The method for preparing the upconversion nanomaterial according to claim 8, characterized in that: The bait source is at least one of bait chloride, erbium nitrate, and bait acetate; the neodymium source is at least one of neodymium chloride, neodymium nitrate, and neodymium acetate; the ytterbium source is at least one of ytterbium chloride, ytterbium nitrate, and ytterbium acetate; the cerium source is at least one of cerium chloride, cerium nitrate, and cerium acetate; the sodium source is at least one of sodium hydroxide and sodium fluoride; and the fluorine source is at least one of ammonium fluoride and ammonium bifluoride.

10. The method for preparing upconversion nanomaterials according to claim 8, characterized in that: In step (2), step (3) and / or step (4), the heating reaction temperature under an inert atmosphere is 270° C.-290° C., and the time is 0.5 h-5 h.

Citation Information

Cited By

  • Rare earth up-conversion luminescent material with three-layer core-shell structure as well as preparation method and application of rare earth up-conversion luminescent material

    CN120118682A